Effect of far-red light exposure on photosynthesis and photoprotection in tomato plants transgenic for the Agrobacterium rhizogenes rolB gene - Bettini, Priscilla P (Journal of plant physiology, 2020)
Copyright © 2019 Elsevier GmbH. All rights reserved.